(untitled) (Annals of Medical Research, 2021)
Aim: Transcatheter aortic valve implantation has been used widely as an alternative treatment method for patients with symptomatic aortic stenosis carrying high surgical risk. Despite technological advances and increased experience, its early and late mortality rate is still relatively high and it is important to predict upcoming cardiac events and mortality for the management of patients. In this study, we aimed to investigate the clinical and laboratory parameters affecting mortality after these procedures performed in our clinic. Material and Methods: The patients who underwent TAVI due to severe AS between May 2015 and March 2019 were investigated retrospectively. Demographic, echocardiographic and laboratory data of all patients were recorded. During the follow-up period (mean: 556 days), patients were divided into 2 groups; deceased patients (group 1, n=13) and living patients (group 2, n=34). The data of the patients before TAVI procedure were compared between the two groups.Results: Among demograhic data, the ratio of chronic kidney disease was significantly higher in the deceased group. Among echo parameters, left ventricular ejection fraction was significantly lower and pulmonary artery pressure was significantly higher in the deceased group. Of laboratory parameters, blood urea nitrogen and creatinine levels were significantly higher and toral protein levels were significantly lower in the deceased group. Additionally, leukocyte, uric acid, CRP and CRP/albumin ratio were significantly higher and albumin was significantly lower in the deceased patients.Conclusion: The presence of chronic kidney disease, low left ventricular EF, high pulmonary artery pressure, high CRP levels, increased CRP/albumin ratio and high uric acid levels preceding TAVI may be helpful to determine the risk of mortality after the TAVI procedure.